Is There a Risk Premium in the Stock Lending Market? Evidence from Equity Options - MURAVYEV, DMITRIY; PEARSON, NEIL D.; POLLET, JOSHUA M. (Journal of Finance, 2022)
ABSTRACT Recent research argues that uncertainty about future stock borrowing fees hinders short‐selling, and this risk explains the performance of short strategies. One possible mechanism is that borrowing fee risk carries a risk premium. Since the present value of the uncertain borrowing fee is reflected in options prices, the difference between option‐implied and realized fees estimates this premium. We find that the risk premium is small. Moreover, if the risk premium is substantial, it should be reflected in the returns to short‐selling stock after adjusting for stock borrowing fees. However, borrowing fee risk does not predict fee‐adjusted returns.